Celebrity worship and impulsive buying: The moderating role of emotional intelligence among indonesian early adult K-Pop fans - Insi Karimiyah; Endah Kurniawati Purwaningtyas; Ali Ridho (Journal of Indonesian Psychological Science (JIPS), 2026)
Impulsive buying has become increasingly prevalent among K-Pop fans, yet the psychological mechanisms underlying this behavior remain insufficiently understood. In particular, limited research has examined the moderating role of emotional intelligence in the relationship between celebrity worship and impulsive buying among early adults. This study investigated whether emotional intelligence moderates the association between celebrity worship and impulsive buying among 268 Indonesian K-Pop fans aged 20–30 years. Data were analyzed using multiple regression and Moderated Regression Analysis (MRA). The overall model was statistically significant and explained 22% of the variance in impulsive buying (R² = .220, p < .001). Celebrity worship and emotional intelligence were both significant predictors of impulsive buying (p < .001). Furthermore, the interaction between celebrity worship and emotional intelligence was significant (B = 0.039, p < .001), indicating a moderating effect. Specifically, higher levels of emotional intelligence weakened the relationship between celebrity worship and impulsive buying, suggesting that emotional intelligence functions as a psychological resource that enhances self-regulation in consumer decision-making. These findings contribute to the literature on fandom behavior and consumer psychology by demonstrating that emotional intelligence can shape the behavioral consequences of celebrity attachment. The results also offer practical implications for counselors, educators, and marketers seeking to promote healthier consumption patterns among fan communities. KEY WORDS: impulse buying; celebrity worship; emotional intelligence; k-pop fans Copyright ©2026. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0